2017
DOI: 10.1308/rcsann.2016.0309
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and predictors of recurrence of Marjolin’s ulcer: experience from Mansoura Universityxs

Abstract: INTRODUCTION Marjolin's ulcer (MU) is an uncommon malignancy occurring on top of old scars. Once thought to be more common in Caucasians, is now detected increasingly in Africa. METHODS This was a retrospective study of patients with MU attending a tertiary centre within Mansoura University (Egypt) from 2004 to 2015. An institutional-based registry of skin and soft-tissue malignancies in this period revealed 560 cases, from which there were 26 cases of MU. RESULTS The most common underlying cause of MU was bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…Thirty‐nine studies reported on metastasis risk of cSCC in the immunocompetent population. Nineteen studies reported on special cohorts in the immunocompetent population, like specific anatomical locations or only reporting on specific high‐risk cSCC or cSCC derived in burns . The results of these specific cohorts are not taken into account in the pooled metastasis risk analyses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐nine studies reported on metastasis risk of cSCC in the immunocompetent population. Nineteen studies reported on special cohorts in the immunocompetent population, like specific anatomical locations or only reporting on specific high‐risk cSCC or cSCC derived in burns . The results of these specific cohorts are not taken into account in the pooled metastasis risk analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen studies reported on special cohorts in the immunocompetent population, like specific anatomical locations or only reporting on specific high-risk cSCC or cSCC derived in burns. [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76] The results of these specific cohorts are not taken into account in the pooled metastasis risk analyses. The details of these studies are shown in Table 2.…”
Section: Studies In Otrmentioning
confidence: 99%
“…Additional risk factors for development of NMSC include radiation therapy, lower Fitzpatrick skin types 1–4, prolonged immunosuppression, human immunodeficiency virus (HIV), human papilloma virus (HPV), and a diagnosis of certain syndromes or genetic disorders [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Unusual changes in peristomal skin of ileostomy and gastrostomy, burn scars, chronic inflammatory dermatologic conditions, and non-healing ulcers should also raise a suspicion for SCC, particularly Majolin’s ulcers [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Moreover, it has been well documented that male gender, tumor location in the trunk and extremities, superficial histologic subtype, younger age at first diagnosis of BCC, and red hair phenotype are associated with a higher risk of having multiple lesions [ 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Brief Overview Of Etiology Risk Factors and Stagingmentioning
confidence: 99%
“…The above findings are consistent with reported literature by Elkins-Williams ST and Marston et al 2 Due to the high risk of nodal metastasis, some authors suggest that, along with physical examinations, an USG of regional node, lymphatic mapping, and sentinel node biopsy could be done. 2,12 Patients with MU pose a therapeutic dilemma; the treatment is very challenging and therapeutic decisions should be taken by a multidisciplinary team. 13,14 The localized disease may be managed by surgery, RT, and/or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%